2014
DOI: 10.1111/tbj.12283
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Lesions of the Breast: Outcomes of 156 Patients Managed without Excisional Biopsy

Abstract: Papillomas of the breast are benign epithelial neoplasms. Because of the low, but continued potential for malignancy, the treatment options after initial diagnosis remain controversial. The aim of this study was to analyze the clinical course of patients with papilloma who were managed by active surveillance following initial diagnosis by core needle biopsy or vacuum-assisted biopsy. This retrospective study analyzed 174 patients with 180 papillomas that were diagnosed by core needle biopsy (113 cases) or vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 25 publications
0
21
1
3
Order By: Relevance
“…Most studies following up VAB excision of PL without atypia did not observe any upgrade to malignancy with at least 2 years of surveillance [60, 62, 63]. One recorded a minimal underestimation of 1.4 % [64] and another 3.2 % [65]. …”
Section: Resultsmentioning
confidence: 99%
“…Most studies following up VAB excision of PL without atypia did not observe any upgrade to malignancy with at least 2 years of surveillance [60, 62, 63]. One recorded a minimal underestimation of 1.4 % [64] and another 3.2 % [65]. …”
Section: Resultsmentioning
confidence: 99%
“…Liberman et al [22] reported that of two upgrades, one was after a biopsy for calcifications while the other one was after biopsy of a mass. The sole upgraded case reported by Wyss et al [49] was after an initial stereotactic biopsy of calcifications. All cases upgraded in our series were associated with calcifications on imaging.…”
Section: Discussionmentioning
confidence: 96%
“…Given that VAB is less invasive, less expensive and quicker to perform, it may be preferred over open biopsy, which is the current gold standard in treating papillary lesions 4 . At our institution, we are experienced in using VAB to treat selective small benign breast tumors (B2 cm).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and treatment of papillary lesions is greatly challenging. Papillomas are usually detected by mammography and ultrasound (US) and subsequently diagnosed by fine needle aspiration (FNA), core needle biopsy (CNB) and vacuum-assisted biopsy (VAB) [4]. Although imaging-guided CNB is a reliable method for the diagnosis of breast lesions, papillary lesions identified at percutaneous biopsy can be difficult to interpret histologically [5].…”
Section: Introductionmentioning
confidence: 99%